The availability of artificial intelligence applications in social studies curricula in basic education schools in the Sultanate of Oman - Al-Saidi, Humaid Muslem Said; Al-Balushi, Fahad Abdullah Mohammed; Al-Kaabi, Mohammed Said Mohammed (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the degree of availability of artificial intelligence applications in social studies curricula in basic education schools in the Sultanate of Oman. It was applied to the social studies curricula for the eleventh and twelfth grades of basic education. The results of the study revealed that the degree of inclusion of artificial intelligence concepts and applications in the content of the eleventh grade social studies curricula in the Sultanate of Oman was weak, reaching (2.88%) in the content of the economic geography book. And the book of social studies with a percentage of (0.86%), and the book of Islamic civilization with a percentage of (0.24%). The results also indicated that the degree of inclusion of artificial intelligence concepts and applications in the content of social studies curricula in the twelfth grade in the Sultanate of Oman was weak, as it reached in the content of the book of geography and modern technologies by (6.55%), the book of social studies by (6.19%), and the book of the world The researchers recommended the inclusion of artificial intelligence concepts and software in the social studies curriculum, and the awareness of social studies teachers through training programs about the importance of teaching using artificial intelligence applications.